Police Duties in the Context of Investigating Child Suspects Resolved through Non-Litigation Legal Efforts (Diversion): Tugas Kepolisian dalam Rangka Penyidikan Tersangka Anak Yang Diselesaikan Melalui Upaya Hukum Non Litigasi (Diversi) - Auliya Rochman (Indonesian Journal of Police Studies, 2021)
This paper tries to discuss the rules and the implementation of the Police Duty in the Context of Investigating a Child Suspect completed through Non-Litigation (Diversion) Legal Efforts. To examine the problem, the research method used is normative legal research methods with the statute approach, and conceptual approach. The results of the research, in police investigations related to child crimes that settle criminal cases outside the court or non-litigation (diversion) must see the case entered restorative justice, and the police not only investigate that the child is a suspect but must also protect all rights owned by the child from violence or discrimination physically or mentally where the rules have been regulated in Article 1 number 2 of Law Number 35 of 2014 concerning Protection Children so that the investigation carried out by the Police of children affected by a criminal case becomes a law that fights for justice and expediency.